(untitled) (American Journal of Islam and Society, 1994)
lbis seminar, sponsored jointly by the International Institute of Islamic Thought and the Waqf Fund of the Kuwaiti Ministry of Awqaf, was held at Herndon, Virginia. Twenty-five papers were presented during the seminar’s eight sessions, which were attended by scores of Arab Muslim scholars and intellectuals from the United States and abroad, either as primary authors of research papers, commentators, or contributors to the serious and in-depth debate that followed each session. Issues of democratization and how to deal with ethnic and sectarian diversity in a context of modem society have become topical and central to the political and intellectual debates in the Arab world. During the past few decades, social and political instability has nndermined profoundly the prospects for progress and prosperity in the Arab world. Pertinent to this instability was the failure to establish consensual policies and institutions in the post-Ottoman era. Hence, questions relating to "traditional" and "modem," "pan-Islamic" and "nationalist," "absolute" and "relative," and "us" and "others" were raised prominently and discussed during the seminar’s five days. The opening session, chaired by Hisham Altalib (IIIT), consisted of three contributions. The first was that of Khalid al Zir (Kuwaiti Ministry of Awqaf), who foc.ussed on the value of research as a higher value and emphasized the role of waqf in Islamic life. Taha J. al ’Alwani (President, lllT), spoke on behalf of IIIT and elaborated on the significance of ...